A non-discriminatory response to disability related problem behaviour at Australian universities. (May 2019) - Dickson, Elizabeth; Duffy, James
Abstract: When students with a psychological disorder study at university, there are competing goals and challenges faced by administrators, teaching staff and students. Positive goals such as inclusion, self-determination and respect for diversity are sometimes counterbalanced by problem behaviour associated with mental illness. The challenge for tertiary institutions is to accommodate the educational needs of students with a psychological disorder, without undermining the inherent requirements of a course of academic study, or the duties that a university owes to staff and students with respect to safe and healthy learning environments. This article considers how the Australian legal system has attempted to find balance between these competing needs and duties, in a way that is respectful to those who study with a psychological disorder.